2016
DOI: 10.1371/journal.pone.0168466
|View full text |Cite
|
Sign up to set email alerts
|

Formaldehyde-Induced Aggravation of Pruritus and Dermatitis Is Associated with the Elevated Expression of Th1 Cytokines in a Rat Model of Atopic Dermatitis

Abstract: Atopic dermatitis is a complex disease of heterogeneous pathogenesis, in particular, genetic predisposition, environmental triggers, and their interactions. Indoor air pollution, increasing with urbanization, plays a role as environmental risk factor in the development of AD. However, we still lack a detailed picture of the role of air pollution in the development of the disease. Here, we examined the effect of formaldehyde (FA) exposure on the manifestation of atopic dermatitis and the underlying molecular me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 38 publications
2
22
0
Order By: Relevance
“…Cutaneous lesions were carefully assessed by scoring systems as previously described . Skin condition at the designated shoulder area was assessed twice, just before the initial application of pullulan hydrogel or RVE@PH (PND 42) and just after the last application (PND 56), to determine changes in the extent and severity of the lesions ( n = 5 per group).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cutaneous lesions were carefully assessed by scoring systems as previously described . Skin condition at the designated shoulder area was assessed twice, just before the initial application of pullulan hydrogel or RVE@PH (PND 42) and just after the last application (PND 56), to determine changes in the extent and severity of the lesions ( n = 5 per group).…”
Section: Methodsmentioning
confidence: 99%
“…Cutaneous lesions were carefully assessed by scoring systems as previously described. 29,36 Skin condition at the designated shoulder area was assessed twice, just before the initial application of pullulan hydrogel or RVE@PH (PND 42) and just after the last application (PND 56), to determine changes in the extent and severity of the lesions (n = 5 per group). We divided all skin lesions within 3 cm 2 of the shoulder into the inspection units (0.25 cm 2 ), inspected and scored the severity of each unit, and summed the scores per unit to yield the total score per rat individual.…”
Section: Dermatitis Scoringmentioning
confidence: 99%
“…Then, we further examined the effects of PB on IL-1β and TNF-α, which are important to accelerate the development of AD 10 . The data showed that PB significantly decreased IL-1β and TNF-α release in the serum and lesional skin of AD mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Only short-term exposure to formaldehyde can cause dysfunction of the skin barrier in children with and without AD; this is more prominent in the latter [ 19 ]. In an experimental rat model of AD, exposure to formaldehyde aggravated pruritus and dermatitis and was associated with an elevated expression of Th1 cytokines [ 20 ]. Exposure to nitrogen dioxide (NO 2 ) at domestic concentrations causes impairment of the skin barrier function in subjects with AD [ 21 ].…”
Section: Discussionmentioning
confidence: 99%